Uranium as a renewable for nuclear energy. (January 2017) - Degueldre, Claude
Abstract: Uranium extraction is the first step of the nuclear fuel cycle. Currently, uranium is only extracted from solid ores such as uranium rich minerals (% level) or minerals such as phosphates (ppm level). For some years extraction of uranium from sea water (ppb level) has been the topic of investigations particularly in Japan due to its national interest. In the huge oceanic volume the amount of uranium is constant, regulated by its river input (soluble) and balanced by its scavenging (particulate) on the sea floor. This work shows that the uranium extraction with parsimony from sea water could be carried in a renewable way if its concentration remains quasi constant. Recommendations for the extraction with use of gel panels or with braid of fabric grafted by sorbing groups in high tide or oceanic pelagic current environments are suggested along with a reduction of the uranium consumption.